2002
DOI: 10.1093/carcin/23.9.1541
|View full text |Cite
|
Sign up to set email alerts
|

Elevated susceptibility of the p53 knockout mouse esophagus to methyl-N-amylnitrosamine carcinogenesis

Abstract: Mutations of the p53 tumor suppressor gene constitute one of the most frequent molecular changes in a wide variety of human cancers, including those in the esophagus. Mice deficient in p53 have recently attracted attention for their potential to identify chemical genotoxins. In this study we investigated the susceptibility of p53 nullizygous (-/-), heterozygous (+/-) and wild-type (+/+) mice to methyl-N-amylnitrosamine (MNAN), which specifically induces esophageal tumors in mice and rats. The p53 (+/-) and (+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Although tumour suppression by p53 is tissue type-dependent, a decrease in dosage of the p53 gene has been shown to promote carcinogen-induced tumorigenesis at many sites, 34,35 including skin, 36 bladder, 37 lung, 38 salivary gland 39 and oesophagus. 40 These studies have shown that p53 is important in controlling early events in oncogenesis in these tissues, but it has not been clear until now that this also applied to colon.…”
Section: Discussionmentioning
confidence: 99%
“…Although tumour suppression by p53 is tissue type-dependent, a decrease in dosage of the p53 gene has been shown to promote carcinogen-induced tumorigenesis at many sites, 34,35 including skin, 36 bladder, 37 lung, 38 salivary gland 39 and oesophagus. 40 These studies have shown that p53 is important in controlling early events in oncogenesis in these tissues, but it has not been clear until now that this also applied to colon.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the pattern of progression from normal mucous to dysplasia, to carcinoma in situ (Shi et al, 1999;Saeki et al, 2002;Shirai et al, 2002). Oesophageal dysplasia is also believed to be one of the precursors for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation status of p53 determines the stability of the protein and controls cell cycle progression, which serves as a master-switch for promoting apoptosis (Ginsberg et al, 1991;Ashcroft and Vousden, 1999;Colman et al, 2000;Asher et al, 2001;Sogame et al, 2003). Alterations of p53 protein, such as missense mutations and loss of its expression caused by nonsense or frame-shift mutations, can result in carcinogenesis (Hussain and Harris, 1998;Medina et al, 2002;Shirai et al, 2002;Nishikawa et al, 2003;Hofseth et al, 2004).…”
Section: Role Of P53 In Uv Irradiation-induced Dna Damagementioning
confidence: 99%